2014
DOI: 10.3109/00016357.2014.968872
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dentin surface treatments including Er,Cr:YSGG laser irradiation with different intensities on the push-out bond strength of the glass fiber posts to root dentin

Abstract: Er,Cr:YSGG laser irradiation with different intensities did not increase the bond strength of the fiber posts to the root canal dentin walls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
1
11
0
3
Order By: Relevance
“…The TAP-RelyX group had the highest bond strength value and the DAP-BisCem group had the lowest bond strength value. The Ca(OH) 2 and TAP medication increased the bond strength of the RelyX resin cement when compared with the control group (p < 0.05). There was no significant difference among the Maxcem groups in terms of bond strength values (p > 0.05).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The TAP-RelyX group had the highest bond strength value and the DAP-BisCem group had the lowest bond strength value. The Ca(OH) 2 and TAP medication increased the bond strength of the RelyX resin cement when compared with the control group (p < 0.05). There was no significant difference among the Maxcem groups in terms of bond strength values (p > 0.05).…”
Section: Resultsmentioning
confidence: 90%
“…[1,2] That is why they require specialized restoration materials. [3] The use of intracanal posts, especially fibre posts, promotes both the retention of the final restoration and the strengthening of the remaining tooth structure.…”
Section: Introductionmentioning
confidence: 99%
“…All ensured that the force was properly applied. Figure 7 presents an experimental set-up images for the push-out test [183]. Figures 7 [183] and 8 [150] presents some examples of testing assembly (push-out bond strength test in Fig.…”
Section: Load Typementioning
confidence: 99%
“…8,17,23,24,25,26,27,28 Chlorhexidine appeared in 3 studies, 18,25,26 although in one of these studies, there was also the presence of chlorhexidine in the composition of a commercial solution called Qmix. 26 Other solutions that were also tested included NaOCl and EDTA used individually, with some variations of time and concentration, 8,16,18,26,27 of which the most used concentrations were 5.25% NaOCl and 17% EDTA both for a maximum of 1 minute. Regarding the methods of activation of the irrigating solutions, 5 studies 18,23,24,27,28 reported using some type of activation method to potentiate the cleaning effect.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…15 Moreover, activation methods of irrigation solutions have been used as an additional method to increase their effectiveness, such as the use of ultrasonic systems and laser devices. 16,17,18 Despite the large number of in vitro studies in the literature, there is currently no consensus on the best solution for removing debris after post-space preparation, while it remains unclearif this can affect the bond strength of FGPs to root dentin. 19 Therefore, the objective of this study was to systematically review the literature using in vitro studies to investigate if cleaning methods of root canal after post-space preparation can increase the retention of FGPs evaluated by push-out test.…”
Section: Introductionmentioning
confidence: 99%